Analysis of a cooling system for robotic joints using a computational fluid dynamics study - Madriz-Ramírez, María Fernanda (2022)
The cooling system is one of the most important parts of a robot, a correct design allows it to increase its capacity while reducing the chances of a malfunction. In general, cooling systems for humanoid robots require special characteristics to not interfere with the optimal operation; aspects such as weight, size, materials, and positioning of this system are crucial for maximum efficiency. The current problem in this design is that the cooling system needs to maintain its power to perform tasks when lifting heavy weights without consequences such as reduced mobility of the joint, and therefore decrease the robot’s efficiency. In this paper, we studied, analyzed, and discarded existing options of electric motor actuators. Once the viable options were obtained, so we proceed to make a proper design, then was made a computational fluid dynamics study (CFD) to get heat extraction measurements as well as fluid velocity, essential to make the final decision, solving the initial problem.